AN OVERVIEW OF IOT BASED INTELLIGENT IRRIGATION SYSTEMS FOR GREENHOUSE: RECENT TRENDS AND CHALLENGES - Ardiansah, Irfan; Bafdal, Nurpilihan; Bono, Awang; Suryadi, Edy; Nurhasanah, Siti (Journal of Applied Engineering Science, 2022)
Food security is an issue that arises as a result of the rising population since population growth decreases agricultural land, leading to water scarcity. Agriculture requires large amounts of water, but water scarcity forces farmers to irrigate their crops with little or low-quality water, leading to the idea of developing smart irrigation. The challenge is how to manage the interactions between plants, growing media, microclimate, and water using manufactured systems. Good irrigation management will minimize the occurrence of poor irrigation design. This review is a way to present various methods and approaches for using sensors, controllers, the Internet of Things, and artificial intelligence in irrigation systems with a focus on improving water use efficiency. The study uses SCOPUS indexed publications and proceedings to study the evolution of irrigation information technology over the last eleven years. We hope this review can serve as a source of information to broaden the validity of the findings of irrigation monitoring and control technologies and help researchers identify future research directions on this subject.